2014
DOI: 10.1530/ec-14-0021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus in patients with acromegaly

Abstract: Early carbohydrate metabolism disorders (ECMDs) and diabetes mellitus (DM) are frequently associated with acromegaly. We aimed to assess the prevalence of ECMDs in patients with acromegaly and to compare the results with those in adults without acromegaly using two population-based epidemiologic surveys. We evaluated 97 patients with acromegaly in several phases of their disease (mean age, 56 years and estimated duration of acromegaly, 12.5 years). An oral glucose tolerance test was done in those not yet diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 20 publications
8
44
0
10
Order By: Relevance
“…DM prevalence has been variably reported (reflecting the series heterogeneity with respect to ethnicity, disease status, age, etc. ), but the highest prevalence rates were 40-52% (Biering et al 2000, Dreval et al 2014; similarly, IGT can be found in up to 28-46% of cases (Biering et al 2000, Kasayama et al 2000.…”
Section: Complicationsmentioning
confidence: 89%
“…DM prevalence has been variably reported (reflecting the series heterogeneity with respect to ethnicity, disease status, age, etc. ), but the highest prevalence rates were 40-52% (Biering et al 2000, Dreval et al 2014; similarly, IGT can be found in up to 28-46% of cases (Biering et al 2000, Kasayama et al 2000.…”
Section: Complicationsmentioning
confidence: 89%
“…The disease activity of GH-producing tumours in patients with acromegaly has been suggested to be associated with visceral adiposity index and insulin sensitivity [18,19]; however, IGF-I correlates more closely than GH with insulin resistance and glucose intolerance [20,21]. Previous studies show that 16% to 52.5% of patients with acromegaly are diagnosed with DM [16,22], with the incidence of DM varying depending on the prospective or retrospective nature of the study, different geographic area, nutritional habits, age, body mass index, and referral pattern [16]. Most studies have shown that among those with GH-producing tumours, survival rates of DM patients are lower than those of non-DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the DM group is older, but there were no gender differences. Data from an Italian group show that active acromegaly in women is strongly associated with higher visceral adiposity dysfunction, insulin resistance, and DM [22]. That elevated GH, IGF-1, and insulin levels in acromegaly are potentially involved in tumour promotion and progression has been a concern for several decades [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…[2,[4][5][6] и специфические для акромегалии (длительность и *e-mail: trigolosova_ira@mail.ru © Коллектив авторов, 2015 активность заболевания, проводимое лечение и т.п.) [2,7,8]. Основной метод лечения акромегалии -хирургический, который, по данным современных исследований [9,10], является не только наиболее эффективным, но и оказывает положительное влия-ние на состояние углеводного обмена.…”
unclassified
“…Можно выделить два класса факторов риска развития СД при акромега-лии: общепопуляционные (возраст, женский пол, наличие артериальной гипертензии, отягощенный анамнез по СД 2-го типа (СД2) и др.) [2,[4][5][6] и специфические для акромегалии (длительность и *e-mail: trigolosova_ira@mail.ru © Коллектив авторов, 2015 активность заболевания, проводимое лечение и т.п.) [2,7,8].…”
unclassified